Elastoplastic constitutive model for hydraulic aperture analysis of hydro-shearing in geothermal energy development. (September 2019) - Xiao, Yong; Guo, Jianchun; Wang, Hehua; Lu, Lize; Chen, Mengting
Geothermal energy is renewable, clean and green energy generated and stored in the Earth's crust. The most important consideration for geothermal energy development in non-hydrothermal scenarios is the use of hydraulic fracturing technology to establish an effective network pathway to conduct fluid from injectors to producers. Hydraulic fracturing in geothermal wells is referred to as hydro-shearing and the aim is to improve the conductivity of natural fractures. In this paper, linear elastic constitutive relationships and shear strength of discontinuities in the pre-peak region are initially considered. Based on the dynamic frictional weakening, a proved conductive aperture and the post-peak elastoplastic constitutive models are proposed to analyze the deformation and conductivity of the natural fracture. Simulation research has shown that the joint compressive strength (JCS) mainly affects the shear displacement and hardly affects the dilation. The joint roughness coefficient (JRC) is more important for decreasing the shear strength and improves the dilation aperture. To no one's surprise, reducing the effective normal stress is the best way for increasing the shear displacement, dilation and conductivity of the natural fracture. Almost 90% of the slip displacement and dilation occurs after fracture shear failure. This displacement not only increases the hydraulic conductivity of the fracture, but also reduces the required surface pumping pressure.